Method for producing propylene-based polymer

A catalyst system with metallocene compounds and a specific block copolymer addresses agglomerate and adhesion issues in propylene polymerization, enhancing productivity and maintaining polymer properties.

JP2025059042APending Publication Date: 2025-04-09JAPAN POLYPROPYLENE CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024166409
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-25
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Conventional methods for producing propylene polymers with long chain branches face issues of agglomerate formation and adhesion to reactor walls, which affect productivity and polymer properties.

Method used

A method involving a specific catalyst system comprising two metallocene compounds and a poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer is used to suppress agglomerate formation and adhesion during polymerization, maintaining the physical properties of the branched propylene-based polymer.

Benefits of technology

The method effectively prevents agglomerate formation and adhesion to reactor walls, improving productivity and maintaining the desired physical properties of the propylene polymer, such as melt tension and branching structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059042000001
    Figure 2025059042000001
  • Figure 2025059042000002
    Figure 2025059042000002
  • Figure 2025059042000003
    Figure 2025059042000003
Patent Text Reader

Abstract

To provide a method for producing a propylene-based polymer which can suppress the clogging of an extraction pipe by suppressing agglomeration and adhesion to the wall surface of the extraction pipe of a polymer powder during polymerization while maintaining the physical properties of a propylene-based polymer having a long chain branch.SOLUTION: There is provided a method for producing a propylene-based polymer which continuously produces propylene in the presence of a catalyst for polymerizing propylene comprising a specific metallocene compound (A-1), a metallocene compound (A-2), a compound forming an ion pair by reacting with the (A-1) and (A-2) or an ion-exchangeable layered silicate salt and an organoaluminum compound (C), wherein a specific poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer is supplied into the polymerization system.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a propylene polymer. [Background technology]

[0002] In recent years, much research has been conducted into introducing a branched structure into polypropylene to improve its suitability for sheet molding, blow molding, thermoforming, foam molding, and other applications that require a material with a relatively high melt tension. Recently, a macromonomer copolymerization method using a metallocene catalyst has been proposed as a method for introducing a branched structure into polypropylene (see, for example, Patent Documents 1 and 2). Propylene-based polymers produced by the macromonomer copolymerization method have the advantage that they are less susceptible to problems such as gel generation and deterioration of extensibility, compared to branched polypropylenes that have been peroxide-modified using a crosslinking aid.

[0003] On the other hand, a method for producing an olefin polymer using a solid catalyst in which two or more transition metal complexes are brought into contact with a solid support is disclosed, which is characterized in that a predetermined amount of at least one compound having an active proton selected from the group consisting of polyalkylene oxide blocks, higher aliphatic amides, polyalkylene oxides, polyalkylene oxide alkyl ethers, alkyldiethanolamines, and polyoxyalkylene alkylamines is supplied to the polymerization system (Patent Document 3). In Patent Document 3, a compound represented by the general formula HO-(CH2CH2O) is used as the polyalkylene oxide block. m -{CH2CH(CH3)O} n -(CH2CH2O) pPatent Document 3 discloses a polyethylene oxide-polypropylene oxide-polyethylene oxide block represented by H. Patent Document 3 provides a method for producing a polyolefin polymer capable of controlling the polymer composition and excellent in moldability and mechanical strength in the production of a polymer intended to introduce long chain branches or broaden the molecular weight distribution, by supplying a predetermined amount of a compound having an active proton. Therefore, Patent Document 3 discloses in the examples that the addition of the polyethylene oxide-polypropylene oxide-polyethylene oxide block changes the ratio of the amounts of polymers produced derived from two types of transition metal complexes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP2009-57542A [Patent Document 2] Patent Publication No. 2020-189966 [Patent Document 3] JP 2014-19825 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the conventional method for producing a propylene polymer having long chain branches by a macromonomer copolymerization method, although it has become possible to obtain a propylene polymer having a high melt tension, there are problems in that agglomerates, particularly of polymer powder, are easily generated in the polymerization system and the polymer powder is easily adhered to the wall surface of a reactor. However, when an additive such as a surfactant is used to solve such a problem in a macromonomer copolymerization method containing two types of metallocene compounds as a catalyst, as described in Patent Document 3, the ratio of the amounts of polymers produced derived from each transition metal complex changes, resulting in a problem that it becomes difficult to produce a propylene-based polymer having the desired long chain branches.

[0006] In view of the above-mentioned state of the art, an object of the present invention is to provide a method for producing a propylene-based polymer by copolymerizing a specific macromonomer, which can suppress the generation of agglomerates of polymer powder and adhesion of the polymer powder to a reactor during polymerization while maintaining the physical properties of a branched propylene-based polymer. [Means for solving the problem]

[0007] The present inventors have found that by combining a catalyst containing two specific metallocene compounds capable of polymerizing a propylene-based polymer having high melt tension long chain branches with a specific poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer (hereinafter sometimes referred to as "PPG-PEG-PPG block copolymer"), it is possible to suppress aggregation of polymer powder and adhesion to a reactor during polymerization while maintaining the physical properties of the branched propylene-based polymer. That is, the present invention relates to the following [1] to [3].

[0008] [1] A process for producing a propylene polymer, comprising continuously polymerizing propylene in the presence of a propylene polymerization catalyst comprising the following components (A-1), (A-2), (B) and (C): A method for producing a propylene-based polymer, comprising feeding a poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer represented by the following general formula (I) into a polymerization system: HO-(C3H6O) a -(C2H4O) b -(C3H6O) c -H···(I) [In the general formula (I), a and c each independently represent an integer of 1 to 60, b represents an integer of 1 to 29, and a+c=2 to 120, and a+b+c≧3 are satisfied.] Component (A-1): A metallocene compound which forms a polymerization catalyst that produces a propylene homopolymer having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is carried out at 70°C. Here, the terminal vinyl ratio (Rv) is defined by the following formula. Rv = (Mn / 42) × [Vi] / 1000 (In the formula, Mn is the number average molecular weight determined by GPC, [Vi] is 1 It is the number of terminal vinyl groups per 1000 monomers calculated by H-NMR.) Component (A-2): A metallocene compound represented by general formula (a2).

[0009] [ka] [In general formula (a2), E 21 and E 22 Q each independently represents a cyclopentadienyl group, an indenyl group, a fluorenyl group, or an azulenyl group, each of which may have a substituent (provided that the substituent is not a heterocyclic group having 4 to 16 carbon atoms and containing nitrogen, oxygen, or sulfur). 21 represents a divalent hydrocarbon group having 1 to 20 carbon atoms, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms; M 21 represents zirconium or hafnium, and X 21 and Y 21 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.] Component (B): A compound or ion-exchangeable layered silicate that reacts with component (A-1) and component (A-2) to form an ion pair. Component (C): Organoaluminum compound. [2] The method for producing a propylene-based polymer according to [1] above, wherein a ratio of the poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer to the amount of propylene fed is 0.1 ppm by mass to 10 ppm by mass. [3] The method for producing a propylene-based polymer according to [1] or [2] above, wherein the poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer is diluted or dissolved in a hydrocarbon solvent, and the resulting solution is joined to a catalyst supply pipe and supplied to a polymerization reactor. Effect of the Invention

[0010] According to the present invention, there can be provided a method for producing a propylene-based polymer by copolymerizing a specific macromonomer, which can suppress the generation of agglomerates of polymer powder and adhesion of the polymer powder to a reactor during polymerization while maintaining the physical properties of the branched propylene-based polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The method for producing a propylene-based polymer of the present invention is a method for producing a propylene-based polymer by continuously polymerizing propylene in the presence of a propylene polymerization catalyst containing the following components (A-1), (A-2), (B) and (C): The method is characterized in that a poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer represented by the following general formula (I) is supplied into the polymerization system. HO-(C3H6O) a -(C2H4O) b -(C3H6O) c -H···(I) [In the general formula (I), a and c each independently represent an integer of 1 to 60, b represents an integer of 1 to 29, and a+c=2 to 120, and a+b+c≧3 are satisfied.] Component (A-1): A metallocene compound which forms a polymerization catalyst that produces a propylene homopolymer having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is carried out at 70°C. Here, the terminal vinyl ratio (Rv) is defined by the following formula. Rv = (Mn / 42) × [Vi] / 1000 (In the formula, Mn is the number average molecular weight determined by GPC, [Vi] is1 It is the number of terminal vinyl groups per 1000 monomers calculated by H-NMR.) Component (A-2): A metallocene compound represented by general formula (a2).

[0012] [ka] [In general formula (a2), E 21 and E 22 Q each independently represents a cyclopentadienyl group, an indenyl group, a fluorenyl group, or an azulenyl group, each of which may have a substituent (provided that the substituent is not a heterocyclic group having 4 to 16 carbon atoms and containing nitrogen, oxygen, or sulfur). 21 represents a divalent hydrocarbon group having 1 to 20 carbon atoms, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms; M 21 represents zirconium or hafnium, and X 21 and Y 21 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.] Component (B): A compound or ion-exchangeable layered silicate that reacts with component (A-1) and component (A-2) to form an ion pair. Component (C): Organoaluminum compound.

[0013] In the method for producing a propylene-based polymer of the present invention, a propylene-containing monomer is polymerized in a state in which the specific PPG-PEG-PPG block copolymer is added to a propylene polymerization catalyst containing the specific two or more kinds of metallocene compounds. This makes it possible to suppress aggregation of polymer powder during polymerization and adhesion of the polymer powder to a reactor while maintaining the physical properties of a propylene-based polymer having long chain branches, such as long chain branches with high melt tension. The adhesion of polymer powder to the reactor may cause problems such as increased load on heat removal and stirring capacity, and blockage of piping, resulting in reduced productivity. In contrast, according to the present invention, the aggregation of polymer powder during polymerization is suppressed, and also adhesion of the polymer powder to the reactor is suppressed, thereby making it possible to suppress the occurrence of the above problems and improve productivity.

[0014] Hereinafter, the process for producing a propylene-based polymer of the present invention will be described in detail for each item. In this specification, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit. In the present invention, the propylene-based polymer is a general term for a propylene homopolymer and a copolymer of propylene and an olefin described below. In addition, in this specification, "wtppm" means ppm by mass, "wt%" means % by mass, and "volppm" means ppm by volume.

[0015] I. Propylene Polymerization Catalysts The propylene polymerization catalyst used in the present invention contains at least the following components (A-1), (A-2), (B) and (C). Component (A-1): A metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer having a terminal vinyl ratio (Rv) of 0.5 or more when propylene is homopolymerized at 70°C. Here, the terminal vinyl ratio (Rv) is defined by the following formula. Rv = (Mn / 42) × [Vi] / 1000 (In the formula, Mn is the number average molecular weight determined by GPC, [Vi] is 1 It is the number of terminal vinyl groups per 1000 monomers calculated by H-NMR.) Component (A-2): a metallocene compound represented by the general formula (a2) Component (B): A compound or ion-exchangeable layered silicate that reacts with components (A-1) and (A-2) to form an ion pair. Component (C): Organoaluminum compound 1. Ingredient (A-1) The component (A-1) is a metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is carried out at 70°C. Here, the terminal vinyl ratio (Rv) is defined by the following formula. Rv = (Mn / 42) × [Vi] / 1000 (In the formula, Mn is the number average molecular weight determined by GPC, [Vi] is 1 It is the number of terminal vinyl groups per 1000 monomers calculated by H-NMR.)

[0016] The terminal structure of the propylene polymer will be described below. In the polymerization of propylene, a chain transfer reaction generally known as β-hydrogen elimination occurs, producing a polymer with a terminal propyl-vinylidene structure (vinylidene structure) as shown in structural formula (1-b). When hydrogen is used, chain transfer usually occurs preferentially to hydrogen, producing a polymer with a terminal i-butyl structure as shown in structural formula (1-d).

[0017] In addition, when a catalyst containing a metallocene compound with a specific structure is used, a special chain transfer reaction called β-methyl elimination occurs, and a polymer having a 1-propenyl structure (vinyl structure) at the end, as shown in structural formula (1-a), is produced (Reference: Macromol. Rapid Commun. 2000, 21, 1103-1107). In addition, the initiation terminals after β-hydrogen elimination and β-methyl elimination are the n-propyl structure shown in structural formula (1-c) and the i-butyl structure shown in structural formula (1-d), respectively, which are saturated hydrocarbon terminals. In other words, the initiation terminal is always a saturated hydrocarbon terminal, and no unsaturated bonds appear at either terminal. As for the terminal structure, it is considered that after extremely rare irregular insertion of propylene, β-hydrogen elimination occurs, resulting in the production of a very small amount of 1-butenyl terminal as shown in structural formula (1-e).

[0018] Furthermore, polymers having the structures shown in structural formulas (1-f) to (1-j) at their terminals may also be produced. The i-butenyl structure of structural formula (1-f) and the 2-butenyl structure of structural formula (1-g) are terminal structures formed by isomerization in extremely rare cases, and their amount is minute compared to the number of the main terminal structures, structural formula (1-a), structural formula (1-b), structural formula (1-c), and structural formula (1-d). In addition, the internal vinylidene structure of structural formula (1-h) is an olefin structure formed inside the polymer chain by further inserting propylene into an intermediate formed by further eliminating hydrogen after the generation of an unsaturated end.

[0019] Among these terminal structures, polymers having the structures shown in structural formula (1-a) and structural formula (1-e) at their terminals can become macromers. Structural formula (1-a) and structural formula (1-e) are the same in that the two carbon atoms at the extreme ends have vinyl structures, and there is no difference in their function of being copolymerizable.

[0020] [ka]

[0021] Component (A-1) of the present invention is a metallocene compound that forms a polymerization catalyst that produces a propylene macromer, and can also be said to be a metallocene compound that forms a catalyst that preferentially produces a polymer whose terminal is represented by structural formula (1-a) or structural formula (1-e).

[0022] The metallocene compound capable of forming a macromer according to the present invention is a metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer that satisfies a terminal vinyl ratio of 0.50 or more when propylene homopolymerization is carried out at 70° C., and is preferably a metallocene compound that is 0.65 or more, more preferably 0.75 or more, and ideally 1.0 (one end of all molecular chains is a vinyl structure). By using a metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer with a higher terminal vinyl ratio, a more efficient macromer synthesis process can be carried out.

[0023] In addition, the polymer having the propyl-vinylidene structure (vinylidene structure) shown in structural formula (1-b) produced as a result of β-hydrogen elimination cannot be copolymerized. Therefore, when a metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer containing a large amount of vinylidene structures is used, the efficiency of producing branched polypropylene is reduced.

[0024] Therefore, the metallocene compound capable of forming a macromer according to the present invention is a metallocene compound in which the terminal vinylidene ratio of the propylene homopolymer formed when propylene homopolymer is polymerized at 70°C is preferably less than 0.1, more preferably less than 0.05, even more preferably less than 0.01, and ideally 0 (substantially no vinylidene structure).

[0025] [Method for evaluating terminal vinyl ratio (Rv)] Here, the polymerization conditions of propylene when determining the terminal vinyl ratio of component (A-1) will be described in detail. After replacing the inside of the 3L autoclave with propylene, 2.86mL of a heptane solution of triisobutylaluminum (143.4mg / mL) is added, 240mL of hydrogen is introduced, and 750g of liquefied propylene is introduced and the temperature is raised to 70℃. Then, the catalyst is pumped into the polymerization tank and polymerization is carried out at 70℃ for 1 hour. Finally, the unreacted propylene is quickly purged to stop the polymerization and obtain a propylene polymer.

[0026] The terminal vinyl ratio (Rv) and terminal vinylidene ratio (Rvd) are 1 The number of terminal vinyl groups [Vi] and the number of terminal vinylidene groups [Vd] obtained from H-NMR are calculated using the following formula as the ratio of polymer chains having each terminal to the total number of polymer chains obtained from the number average molecular weight (Mn) determined by GPC. Rv = (Mn / 42) × [Vi] / 1000 Rvd = (Mn / 42) × [Vd] / 1000 (Note that Mn is the number average molecular weight determined by GPC.)

[0027] [Method of measuring number average molecular weight (Mn)] In the present invention, the number average molecular weight (Mn) refers to one measured by gel permeation chromatography (GPC). The baseline and intervals of the obtained chromatogram are as shown in Figure 1. The retention volume is converted into the molecular weight using a calibration curve based on a previously prepared standard polystyrene. The standard polystyrene used is the following brand manufactured by Tosoh Corporation. F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, A1000 A calibration curve is prepared by injecting 0.2 mL of a solution in o-dichlorobenzene (containing 0.5 mg / mL BHT) at a concentration of 0.5 mg / mL. The calibration curve is a cubic equation obtained by approximating with the least squares method. The viscosity equation used for conversion to molecular weight is [η] = K × M α The following values ​​are used: PS:K=1.38×10 -4 α=0.7 PP:K = 1.03 x 10 -4 α=0.78 The GPC measurement conditions are as follows: Apparatus: WATERS GPC (ALC / GPC 150C) Detector: FOXBORO MIRAN1AIR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AD806M / S (3 columns) Mobile phase solvent: ο-dichlorobenzene Measurement temperature: 140℃ Flow rate: 1.0ml / min Injection amount: 0.2ml Sample Preparation: Prepare a 1 mg / mL solution of the sample using o-dichlorobenzene (containing 0.5 mg / mL BHT) and dissolve the sample at 140° C. for approximately 1 hour.

[0028] [Method for measuring the number of unsaturated ends] Where: 1 Details of the method for measuring the number of terminal vinyl groups [Vi] and the number of terminal vinylidene groups [Vd] by H-NMR are as follows. [Sample preparation and measurement conditions] 200 mg of sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of o-dichlorobenzene / deuterated bromide benzene (C6D5Br) = 4 / 1 (volume ratio) and hexamethyldisiloxane, a chemical shift standard substance, and dissolved uniformly in a block heater at 150 °C. NMR measurements are performed using a Bruker Biospin AV400 NMR device equipped with a 10 mm φ cryoprobe. To quantify unsaturated ends, 1 H-NMR is used. 1 The H-NMR measurement conditions are a sample temperature of 120°C, a pulse angle of 4.5°, a pulse interval of 2 seconds, and an accumulation count of 512. The chemical shift is set to 0.09 ppm for the proton signal of hexamethyldisiloxane, and the chemical shifts of the signals due to other protons are based on this.

[0029] [How to calculate the number of unsaturated ends] 1 In H-NMR, the proton signals of the 1-propenyl structure of structural formula (1-a) and the 1-butenyl structure of structural formula (1-e) are 1 It is detected overlapping with the signals of 5.08-4.85 ppm and 5.86-5.69 ppm in the H-NMR spectrum. Therefore, the number of terminal vinyl groups [Vi] is the total number of 1-propenyl structures and 1-butenyl structures, and the amount of unsaturated bonds per 1000 monomers is given by 1 It is calculated from the signal intensity of the H-NMR spectrum according to the following formula. Structural formula (1-a) + structural formula (1-e): [Vi] = Ivi × 1000 / Itotal. The number of terminal vinylidene groups [Vd] is the amount of unsaturated bonds per 1000 monomers, as follows: 1 It is calculated from the signal intensity of the H-NMR spectrum according to the following formula. Structural formula (1-b): [Vd]=Ivd×1000 / Itotal Here, Ivi and Ivd represent characteristic values ​​of signals based on structural formula (1-a), structural formula (1-e), and structural formula (1-b), respectively, and are quantities represented by the following formulas. Ivi=(I 5.08~4.85 +I 5.86~5.69 ) / 3, Ivd=(I 4.79~4.65 ) / 2, I is the integrated intensity, and the subscripts of I indicate the range of chemical shifts. For example, I 5.08~4.85 indicates the integrated intensity of the signal detected between 5.08 ppm and 4.85 ppm. In addition, Itotal is the amount shown by the following formula. Itotal=IC3+Ivi+Ivd+Iibu+Ivnl+Iivd Here, Iibu, Ivnl, and Iivd respectively represent characteristic values ​​of signals based on structural formula (1-f): i-butenyl, structural formula (1-g): 2-butenyl, and structural formula (1-h): internal vinylidene structure, and are quantities represented by the following formulas. Iibu=I 5.30~5.08 , Ivnl = (I 5.58~5.30 ) / 2, Iivd = (I 4.85~4.79 ) / 2 IC3 represents a characteristic value of a signal based on propylene and is the quantity shown by the following formula. IC3 = 1 / 6×Imain What is Imain? 1 It is the sum of the proton signals of the polymer main chain and saturated terminals detected in the H-NMR spectrum from 4.00 to 0.00 ppm. In addition, in Itotal, peaks derived from other olefin structures produced as by-products in the range other than the above, such as internal tri-substituted olefins represented by structural formula (1-i) and internal vinylenes represented by structural formula (1-j), may be detected at a small level, and in such cases, these are excluded from the calculation.

[0030] Component (A-1) is not particularly limited as long as it is a metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer that satisfies a terminal vinyl ratio of 0.50 or more when propylene homopolymerization is performed at 70° C., and can also be selected from compounds included in general formula (a2) of component (A-2) described below. Component (A-1) can be a bisindene complex having a bulky heterocyclic group at the 2-position and an optionally substituted aryl group or a nitrogen-, oxygen- or sulfur-containing heterocyclic group at the 4-position, and the following structure can be given as one of non-limiting preferred embodiments. The component (A-1) is preferably a metallocene compound represented by the following general formula (a1) from the viewpoint of producing a propylene-based polymer having a high terminal vinyl ratio.

[0031] [ka]

[0032] [In general formula (a1), R 11 and R 12 R each independently represents a heterocyclic group containing nitrogen, oxygen or sulfur and having 4 to 16 carbon atoms. 13 and R 14 Q each independently represents an aryl group having 6 to 30 carbon atoms which may contain halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or a plurality of hetero elements selected from these, or a heterocyclic group having 6 to 16 carbon atoms which contains nitrogen, oxygen, or sulfur. 11 represents a divalent hydrocarbon group having 1 to 20 carbon atoms, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms; M 11 represents zirconium or hafnium, and X 11 and Y 11 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.]

[0033] Above R 11 and R 12 The nitrogen-, oxygen- or sulfur-containing heterocyclic group having 4 to 16 carbon atoms is preferably a 2-furyl group, a substituted 2-furyl group, a substituted 2-thienyl group or a substituted 2-furfuryl group, and more preferably a substituted 2-furyl group. R 11 and R 12 is a group selected from heterocyclic groups containing nitrogen, oxygen, or sulfur and having 4 to 16 carbon atoms, the terminal vinyl ratio (Rv) can be increased. In particular, by introducing a substituent of an appropriate size onto the heterocyclic group, the relative positional relationship between the heterocycle and the coordination field on the transition metal and the growing polymer chain can be made appropriate, thereby making it possible to further increase the terminal vinyl ratio (Rv). In addition, examples of the substituent of the substituted 2-furyl group, the substituted 2-thienyl group, and the substituted 2-furfuryl group include an alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, or a propyl group, a halogen atom, such as a fluorine atom or a chlorine atom, an alkoxy group having 1 to 6 carbon atoms, such as a methoxy group or an ethoxy group, and a trialkylsilyl group. Among these, a methyl group or a trimethylsilyl group is preferred, and a methyl group is particularly preferred. In addition, R 11 and R 12 Particularly preferred as R is a 5-methyl-2-furyl group. 11 and R 12 are preferably identical to each other.

[0034] Above R 13 and R 14 are each independently an aryl group having 6 to 30 carbon atoms which may contain halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or a plurality of hetero elements selected from these, or a heterocyclic group having 6 to 16 carbon atoms which contains nitrogen, oxygen, or sulfur. In particular, R 13 and R 14 By increasing the bulkiness, it is possible to obtain a propylene-based polymer having higher stereoregularity, fewer heterogeneous bonds, and a higher terminal vinyl ratio. So, R 13 and R14 is preferably an aryl group having one or more hydrocarbon groups having 1 to 6 carbon atoms, silyl groups having a hydrocarbon group having 1 to 6 carbon atoms, halogen-containing hydrocarbon groups having 1 to 6 carbon atoms, or aryl groups which may have a halogen atom as a substituent on an aryl ring skeleton, in the range of 6 to 16 carbon atoms, and such R 13 and R 14 Specific examples of the aryl group include a 4-t-butylphenyl group, a 2,3-dimethylphenyl group, a 3,5-di-t-butylphenyl group, a 4-chlorophenyl group, a 4-trimethylsilylphenyl group, a 1-naphthyl group, and a 2-naphthyl group. Also, R 13 and R 14 More preferably, R is a phenyl group having one or more hydrocarbon groups having 1 to 6 carbon atoms, silyl groups having a hydrocarbon group having 1 to 6 carbon atoms, halogen-containing hydrocarbon groups having 1 to 6 carbon atoms, or halogen atoms as substituents, with the carbon number being in the range of 6 to 16. The position of substitution is preferably the 4-position on the phenyl group. 13 and R 14 Specific examples of R include a 4-t-butylphenyl group, a 4-biphenylyl group, a 4-chlorophenyl group, and a 4-trimethylsilylphenyl group. 13 and R 14 are preferably identical to each other.

[0035] Above X 11 and Y 11 is an auxiliary ligand, and reacts with component (B) to produce an active metallocene having olefin polymerization ability. Therefore, as long as this purpose is achieved, X 11 and Y 11 There are no limitations on the type of ligand, and each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an oxygen-containing hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.

[0036] Above Q 11represents a divalent hydrocarbon group having 1 to 20 carbon atoms linking two five-membered rings, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms. When two hydrocarbon groups are present on the above-mentioned silylene group or germylene group, they may be linked to each other to form a ring structure. Above Q 11 Specific examples of the alkylene group include alkylene groups such as methylene, methylmethylene, dimethylmethylene, and 1,2-ethylene; aryl alkylene groups such as diphenylmethylene; silylene groups; alkylsilylene groups such as methylsilylene, dimethylsilylene, diethylsilylene, di(n-propyl)silylene, di(i-propyl)silylene, and di(cyclohexyl)silylene; (alkyl)(aryl)silylene groups such as methyl(phenyl)silylene; arylsilylene groups such as diphenylsilylene; alkyloligosilylene groups such as tetramethyldisilylene; germylene groups; alkylgermylene groups in which the silicon of the silylene group having the above-mentioned divalent hydrocarbon group having 1 to 20 carbon atoms is replaced with germanium; (alkyl)(aryl)germylene groups; and arylgermylene groups. Among these, a silylene group having a hydrocarbon group of 1 to 20 carbon atoms or a germylene group having a hydrocarbon group of 1 to 20 carbon atoms is preferred, with an alkylsilylene group and an alkylgermylene group being particularly preferred.

[0037] The above M 11 is zirconium or hafnium, preferably hafnium.

[0038] Among the compounds represented by the above general formula (a1), the following are specific examples of preferred compounds. However, to avoid a large number of complicated examples, only representative example compounds are described. In addition, although compounds with hafnium as the central metal are described, similar zirconium compounds can also be used, and it is self-evident that various ligands, cross-linking groups, or auxiliary ligands can be used arbitrarily. (1) dichloro[1,1'-dimethylsilylenebis{2-(2-furyl)-4-phenyl-indenyl}]hafnium, (2) dichloro[1,1'-dimethylsilylenebis{2-(2-thienyl)-4-phenyl-indenyl}]hafnium, (3) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-phenyl-indenyl}]hafnium, (4) dichloro[1,1'-diphenylsilylenebis{2-(5-methyl-2-furyl)-4-phenyl-indenyl}]hafnium, (5) dichloro[1,1'-dimethylgermylenebis{2-(5-methyl-2-furyl)-4-phenyl-indenyl}]hafnium, (6) dichloro[1,1'-dimethylgermylenebis{2-(5-methyl-2-thienyl)-4-phenyl-indenyl}]hafnium, (7) dichloro[1,1'-dimethylsilylenebis{2-(5-t-butyl-2-furyl)-4-phenyl-indenyl}]hafnium, (8) dichloro[1,1'-dimethylsilylenebis{2-(5-trimethylsilyl-2-furyl)-4-phenyl-indenyl}]hafnium, (9) dichloro[1,1'-dimethylsilylenebis{2-(5-phenyl-2-furyl)-4-phenyl-indenyl}]hafnium, (10) dichloro[1,1'-dimethylsilylenebis{2-(4,5-dimethyl-2-furyl)-4-phenyl-indenyl}]hafnium, (11) dichloro[1,1'-dimethylsilylenebis{2-(2-benzofuryl)-4-phenyl-indenyl}]hafnium, (12) dichloro[1,1'-dimethylsilylenebis{2-(2-furfuryl)-4-phenyl-indenyl}]hafnium, (13) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-chlorophenyl)-indenyl}]hafnium, (14) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-fluorophenyl)-indenyl}]hafnium, (15) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-trifluoromethylphenyl)-indenyl}]hafnium, (16) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropyl-phenyl)-indenyl}]hafnium, (17) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-t-butylphenyl)-indenyl}]hafnium, (18) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-trimethylsilylphenyl)-indenyl}]hafnium, (19) dichloro[1,1'-dimethylsilylenebis{2-(2-furyl)-4-(1-naphthyl)-indenyl}]hafnium, (20) dichloro[1,1'-dimethylsilylenebis(2-(2-furyl)-4-(2-naphthyl)-indenyl)]hafnium, (21) dichloro[1,1'-dimethylsilylenebis(2-(2-furyl)-4-(2-phenanthryl)-indenyl)]hafnium, (22) dichloro[1,1'-dimethylsilylenebis(2-(2-furyl)-4-(9-phenanthryl)-indenyl)]hafnium, (23) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-biphenylyl)-indenyl}]hafnium, (24) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(1-naphthyl)-indenyl}]hafnium, (25) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(2-naphthyl)-indenyl}]hafnium, (26) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(2-phenanthryl)-indenyl}]hafnium, (27) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(9-phenanthryl)-indenyl}]hafnium, (28) dichloro[1,1'-dimethylsilylenebis{2-(5-t-butyl-2-furyl)-4-(1-naphthyl)-indenyl}]hafnium, (29) dichloro[1,1'-dimethylsilylenebis{2-(5-t-butyl-2-furyl)-4-(2-naphthyl)-indenyl}]hafnium, (30) dichloro[1,1'-dimethylsilylenebis{(2-(5-t-butyl-2-furyl)-4-(2-phenanthryl)-indenyl)}hafnium, (31) dichloro[1,1'-dimethylsilylenebis{2-(5-t-butyl-2-furyl)-4-(9-phenanthryl)-indenyl}]hafnium, (32) dichloro[1,1'-dimethylsilylene(2-methyl-4-phenyl-indenyl){2-(5-methyl-2-furyl)-4-phenyl-indenyl}]hafnium, (33) Dichloro[1,1'-dimethylsilylene(2-methyl-4-phenyl-indenyl){2-(5-methyl-2-thienyl)-4-phenyl-indenyl}]hafnium, and the like.

[0039] Of these, more preferred are: (3) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-phenyl-indenyl}]hafnium, (13) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-chlorophenyl)-indenyl}]hafnium, (16) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropyl-phenyl)-indenyl}]hafnium, (17) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-t-butylphenyl)-indenyl}]hafnium, (18) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-trimethylsilylphenyl)-indenyl}]hafnium, (23) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-biphenylyl)-indenyl}]hafnium, (25) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(2-naphthyl)-indenyl}]hafnium, It is.

[0040] Also particularly preferred are (13) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-chlorophenyl)-indenyl}]hafnium, (16) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropyl-phenyl)-indenyl}]hafnium, (17) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-t-butylphenyl)-indenyl}]hafnium, (18) dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-trimethylsilylphenyl)-indenyl}]hafnium, It is.

[0041] 2. Component (A-2) The component (A-2) is a metallocene compound represented by the following general formula (a2).

[0042] [ka]

[0043] [In general formula (a2), E 21 and E 22Q each independently represents a cyclopentadienyl group, an indenyl group, a fluorenyl group, or an azulenyl group, each of which may have a substituent (provided that the substituent is not a heterocyclic group having 4 to 16 carbon atoms and containing nitrogen, oxygen, or sulfur). 21 represents a divalent hydrocarbon group having 1 to 20 carbon atoms, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms; M 21 represents zirconium or hafnium, and X 21 and Y 21 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.]

[0044] Above E 21 and E 22 are each independently a cyclopentadienyl group, an indenyl group, a fluorenyl group, or an azulenyl group, each of which may have a substituent. However, the substituent is not a heterocyclic group containing nitrogen, oxygen or sulfur and having 4 to 16 carbon atoms. Of these, a substituted cyclopentadienyl group, a substituted indenyl group, and a substituted azulenyl group are preferable. Examples of the substituent include a hydrocarbon group having 1 to 6 carbon atoms, a halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or an aryl group having 6 to 30 carbon atoms which may contain a plurality of hetero elements selected from these, a halogen atom, an alkoxy group, a trialkylsilyl group, and the like. The hydrocarbon group having 1 to 6 carbon atoms includes R 21 and R 22 The aryl group having 6 to 30 carbon atoms, which may contain halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or a plurality of hetero elements selected therefrom, may be the same as the hydrocarbon group having 1 to 6 carbon atoms in the general formula (a3) ​​described later. 23 and R 24In the above, the aryl group may be the same as the aryl group having 6 to 30 carbon atoms which may contain halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or a plurality of hetero elements selected therefrom. Examples of the halogen atom include a fluorine atom and a chlorine atom, examples of the alkoxy group having 1 to 6 carbon atoms include a methoxy group and an ethoxy group, and examples of the trialkylsilyl group include a trimethylsilyl group.

[0045] Above X 21 and Y 21 is an auxiliary ligand, and reacts with component (B) as a cocatalyst to produce an active metallocene having olefin polymerization ability. Therefore, as long as this purpose is achieved, X 21 and Y 21 There are no limitations on the type of ligand, and each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an oxygen-containing hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.

[0046] Q 21 represents a divalent hydrocarbon group having 1 to 20 carbon atoms linking two rings, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms. When two hydrocarbon groups are present on the above-mentioned silylene group or germylene group, they may be linked to each other to form a ring structure.

[0047] The above Q 21Specific examples of the alkylene group include alkylene groups such as methylene, methylmethylene, dimethylmethylene, and 1,2-ethylene; aryl alkylene groups such as diphenylmethylene; silylene groups; alkyl silylene groups such as methylsilylene, dimethylsilylene, diethylsilylene, di(n-propyl)silylene, di(i-propyl)silylene, and di(cyclohexyl)silylene; (alkyl)(aryl)silylene groups such as methyl(phenyl)silylene; aryl silylene groups such as diphenylsilylene; alkyl oligosilylene groups such as tetramethyldisilylene; germylene groups; alkylgermylene groups in which the silicon of the silylene group having the above-mentioned divalent hydrocarbon group having 1 to 20 carbon atoms is replaced with germanium; (alkyl)(aryl)germylene groups; and arylgermylene groups. Among these, a silylene group having a hydrocarbon group of 1 to 20 carbon atoms or a germylene group having a hydrocarbon group of 1 to 20 carbon atoms is preferred, with an alkylsilylene group and an alkylgermylene group being particularly preferred.

[0048] The above M 21 is zirconium or hafnium, preferably hafnium.

[0049] As component (A-2), a compound that forms a polymerization catalyst capable of copolymerizing a propylene monomer with a propylene macromer is preferred, and such a compound may also be a compound that forms a catalyst capable of producing a propylene macromer at the same time. Component (A-2) is preferably a metallocene compound represented by the following general formula (a3) ​​from the viewpoint of ease of copolymerization with the propylene macromer generated from component (A-1).

[0050] [ka]

[0051] [In general formula (a3), R 21 and R 22 R is each independently a hydrocarbon group having 1 to 6 carbon atoms. 23 and R 24Q each independently represents an aryl group having 6 to 30 carbon atoms which may contain halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or a plurality of hetero elements selected therefrom. 21 represents a divalent hydrocarbon group having 1 to 20 carbon atoms, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms; M 21 represents zirconium or hafnium, and X 21 and Y 21 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.]

[0052] Above R 21 and R 22 are each independently a hydrocarbon group having 1 to 6 carbon atoms, preferably an alkyl group, and more preferably an alkyl group having 1 to 4 carbon atoms. Specific examples include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, sec-butyl, n-pentyl, i-pentyl, n-hexyl, and the like, and are preferably methyl, ethyl, or n-propyl.

[0053] In addition, the above R 23 and R 24are each independently an aryl group having 6 to 30 carbon atoms, preferably 6 to 24 carbon atoms, which may contain halogen, silicon, oxygen, sulfur, nitrogen, boron, phosphorus, or a plurality of hetero elements selected from these. Such aryl groups are phenyl groups, biphenylyl groups, and naphthyl groups, which may have a substituent. Preferred examples include phenyl, 3-chlorophenyl, 4-chlorophenyl, 3-fluorophenyl, 4-fluorophenyl, 4-methylphenyl, 4-i-propylphenyl, 4-t-butylphenyl, 4-trimethylsilylphenyl, 4-(2-fluoro-4-biphenylyl), 4-(2-chloro-4-biphenylyl), 1-naphthyl, 2-naphthyl, 4-chloro-2-naphthyl, 3-methyl-4-trimethylsilylphenyl, 3,5-dimethyl-4-t-butylphenyl, 3,5-dimethyl-4-trimethylsilylphenyl, and 3,5-dichloro-4-trimethylsilylphenyl. In general formula (a3), Q 21 , M 21 , X 21 and Y 21 are Q in general formula (a2), 21 , M 21 , X 21 and Y 21 It may be the same as:

[0054] Non-limiting examples of the metallocene compound represented by the above general formula (a3) ​​include the following. However, to avoid a large number of complicated examples, only representative example compounds are described. Also, although compounds having hafnium as a central metal are described, similar zirconium compounds can also be used, and it is self-evident that various ligands, bridging groups, or auxiliary ligands can be used as desired. (1) dichloro{1,1'-dimethylsilylenebis(2-methyl-4-phenyl-4-hydroazulenyl)}hafnium, (2) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium, (3) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-t-butylphenyl)-4-hydroazulenyl}]hafnium, (4) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, (5) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(3-chloro-4-t-butylphenyl)-4-hydroazulenyl}]hafnium, (6) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(3-methyl-4-t-butylphenyl)-4-hydroazulenyl}]hafnium, (7) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(3-chloro-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, (8) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(3-methyl-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, (9) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(1-naphthyl)-4-hydroazulenyl}]hafnium, (10) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(2-naphthyl)-4-hydroazulenyl}]hafnium, (11) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chloro-2-naphthyl)-4-hydroazulenyl}]hafnium, (12) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(2-fluoro-4-biphenylyl)-4-hydroazulenyl}]hafnium, (13) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(2-chloro-4-biphenylyl)-4-hydroazulenyl}]hafnium, (14) dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(9-phenanthryl)-4-hydroazulenyl}]hafnium, (15) dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium, (16) dichloro[1,1'-dimethylsilylenebis{2-n-propyl-4-(3-chloro-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, (17) dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(3-chloro-4-t-butylphenyl)-4-hydroazulenyl}]hafnium, (18) dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(3-methyl-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, (19) dichloro[1,1'-dimethylgermylenebis{2-methyl-4-(2-fluoro-4-biphenylyl)-4-hydroazulenyl}]hafnium, (20) dichloro[1,1'-dimethylgermylenebis{2-methyl-4-(4-t-butylphenyl)-4-hydroazulenyl}]hafnium, (21) dichloro[1,1'-(9-silafluorene-9,9-diyl)bis{2-ethyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium, (22) dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(4-chloro-2-naphthyl)-4-hydroazulenyl}]hafnium, (23) dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(2-fluoro-4-biphenylyl)-4-hydroazulenyl}]hafnium, (24) Dichloro[1,1'-(9-silafluorene-9,9-diyl)bis{2-ethyl-4-(3,5-dichloro-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, and the like.

[0055] Among these, preferred are dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium, dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(3-chloro-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(2-fluoro-4-biphenylyl)-4-hydroazulenyl}]hafnium, and dichloro[1, 1'-dimethylsilylenebis{2-ethyl-4-(4-chloro-2-naphthyl)-4-hydroazulenyl}]hafnium, dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(3-methyl-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, dichloro[1,1'-(9-silafluorene-9,9-diyl)bis{2-ethyl-4-(3,5-dichloro-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium.

[0056] Also particularly preferred are dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium, dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(2-fluoro-4-biphenylyl)-4-hydroazulenyl}]hafnium, dichloro[1,1'-dimethylsilylenebis{2-ethyl-4-(3-methyl-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium, and dichloro[1,1'-(9-silafluorene-9,9-diyl)bis{2-ethyl-4-(3,5-dichloro-4-trimethylsilylphenyl)-4-hydroazulenyl}]hafnium.

[0057] 3.Component (B) Component (B) is a compound or an ion-exchangeable layered silicate that reacts with components (A-1) and (A-2) to form an ion pair. The component (B) may be used alone or in combination of two or more thereof, and is preferably an ion-exchangeable layered silicate.

[0058] 3-1. Compounds that form ion pairs with component (A-1) and component (A-2) Examples of the compound that reacts with component (A-1) and component (A-2) to form an ion pair include aluminum oxy compounds and boron compounds. Specific examples of the aluminum oxy compounds include compounds represented by the following general formulas (I) to (III).

[0059] [ka]

[0060] In the above general formulas (I), (II) and (III), R 91 , R 101 and R 111 represents a hydrogen atom or a hydrocarbon group, preferably a hydrocarbon group having 1 to 10 carbon atoms, and particularly preferably a hydrocarbon group having 1 to 6 carbon atoms. 91 , R 101 and R 111 may be the same or different, and p represents an integer of 0 to 40, preferably 2 to 30. The compounds represented by the general formulas (I) and (II) are also called aluminoxanes, and among them, methylaluminoxane or methylisobutylaluminoxane is preferred. The above aluminoxanes can be used in combination of multiple types within each group and between each group. The above aluminoxanes can be prepared under various known conditions. In general formula (III), R 112 represents a hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms. The compound represented by the general formula (III) is a compound represented by the general formula R 112 It can be obtained by reacting with an alkylboronic acid represented by B(OH)2 in a molar ratio of 10:1 to 1:1. Examples of the boron compound include complexes of cations such as carbonium cation and ammonium cation with organic boron compounds such as triphenyl boron, tris(3,5-difluorophenyl) boron and tris(pentafluorophenyl) boron, and various organic boron compounds such as tris(pentafluorophenyl) boron.

[0061] 3-2. Ion-exchange layered silicate An ion-exchangeable layered silicate (hereinafter sometimes simply referred to as silicate) is a silicate compound that has a crystal structure in which layers formed by ionic bonds or the like are stacked in parallel with each other through bonding forces, has interlayer ions between the layers, and the interlayer ions contained therein are exchangeable. Most silicates occur naturally as the main component of clay minerals. They are generally purified by dispersing / swelling them in water and measuring the difference in sedimentation rate, but it is not necessary to completely remove impurities, and they may contain impurities other than ion-exchangeable layered silicates (quartz, cristobalite, etc.). Depending on the type, amount, particle size, crystallinity, and dispersion state of these impurities, they may be more preferable than pure silicates, and such complexes are also included in the ion-exchangeable layered silicates of component (B). Moreover, the silicate used in the present invention is not limited to naturally occurring silicates, but may be synthetically produced silicates.

[0062] Specific examples of ion-exchangeable layered silicates include layered silicates having a 1:1 type structure or a 2:1 type structure, as described in "Clay Mineralogy" by Shiramizu Haruo, Asakura Publishing (1988). The 1:1 type structure refers to a structure based on stacking of one layer of tetrahedral sheet and one layer of octahedral sheet, as described in the above-mentioned "Clay Mineralogy" and the like. The 2:1 type structure refers to a structure based on stacking two layers of tetrahedral sheets sandwiching one layer of octahedral sheet. Specific examples of ion-exchangeable layered silicates having a 1:1 type structure include kaolin group silicates such as dickite, nacrite, kaolinite, metahalloysite, and halloysite, and serpentine group silicates such as chrysotile, lisardite, and antigorite. Specific examples of ion-exchangeable layered silicates having a 2:1 type structure include smectite group silicates such as montmorillonite, beidellite, nontronite, saponite, hectorite, stevensite, etc., vermiculite group silicates such as vermiculite, mica group silicates such as mica, illite, sericite, glauconite, etc., attapulgite, sepiolite, palygorskite, bentonite, pyrophyllite, talc, chlorite group, etc. These may form mixed layers. Among these, it is preferable that the main component is an ion-exchangeable layered silicate having a 2:1 type structure, more preferably that the main component is a smectite group silicate, and even more preferably that the main component is montmorillonite. The type of interlayer cation (the positive ion contained between the layers of the ion-exchangeable layered silicate) is not particularly limited, but preferred main components are alkali metals in Group 1 of the periodic table, such as lithium and sodium, alkaline earth metals in Group 2 of the periodic table, such as calcium and magnesium, and transition metals, such as iron, cobalt, copper, nickel, zinc, ruthenium, rhodium, palladium, silver, iridium, platinum, and gold, which are relatively easily available.

[0063] The ion-exchangeable layered silicate may be used in a dry state or in a liquid slurried state. The shape of the ion-exchangeable layered silicate is not particularly limited, and may be a naturally occurring shape or a shape at the time of artificial synthesis, or may be an ion-exchangeable layered silicate whose shape has been processed by operations such as pulverization, granulation, and classification. Among these, the use of granulated ion-exchange layered silicate is particularly preferred because it gives good polymer particle properties when the ion-exchange layered silicate is used as a catalyst component. For the method of treating the ion-exchanged layered silicate, reference can be made to the description in paragraphs 0042 to 0071 of JP-A-2009-299046.

[0064] The component (B) preferably used in the present invention is a chemically treated ion-exchangeable layered silicate, and has an Al / Si atomic ratio of 0.01 to 0.25, preferably 0.03 to 0.24, and more preferably 0.05 to 0.23. The Al / Si atomic ratio is considered to be an index of the acid treatment strength of the clay portion. The aluminum and silicon in the ion-exchange layered silicate are measured by creating a calibration curve according to the JIS method of chemical analysis and quantifying with fluorescent X-rays.

[0065] 4.Component (C) The component (C) of the propylene polymerization catalyst used in the present invention is an organoaluminum compound. As the organoaluminum compound, an organoaluminum compound represented by the following general formula (4) is preferably used. (AlR n X 3-n ) m ...General formula (IV) In the above general formula (IV), R represents an alkyl group having 1 to 20 carbon atoms, X represents a halogen, a hydrogen, an alkoxy group or an amino group, n represents an integer of 1 to 3, and m represents an integer of 1 to 2. ] The organoaluminum compounds may be used alone or in combination of two or more kinds. Specific examples of the organoaluminum compound include trimethylaluminum, triethylaluminum, tri-normal propylaluminum, tri-normal butylaluminum, triisobutylaluminum, tri-normal hexylaluminum, tri-normal octylaluminum, tri-normal decylaluminum, diethylaluminum chloride, diethylaluminum sesquichloride, diethylaluminum hydride, diethylaluminum ethoxide, diethylaluminum dimethylamide, diisobutylaluminum hydride, diisobutylaluminum chloride, etc. Among these, preferred are trialkylaluminum and alkylaluminum hydrides in which m=1 and n=3. More preferred are trialkylaluminums in which R has 1 to 8 carbon atoms.

[0066] 5. Catalyst Preparation The propylene polymerization catalyst preferably used in the present invention contains the above-mentioned components (A-1), (A-2), (B) and (C), which can be obtained by contacting them in or outside a polymerization vessel. The amounts of the components (A-1), (A-2), (B) and (C) used are arbitrary. For example, the total amount of the components (A-1) and (A-2) used is preferably in the range of 0.1 μmol to 1000 μmol, and more preferably 0.5 μmol to 500 μmol, per 1 g of the component (B). The amount of component (C) used is preferably 0.01 to 5×10 in terms of the molar ratio of aluminum in component (C) to the total transition metals in components (A-1) and (A-2). 6 , more preferably 0.1 to 1×10 4 The range is. The order of contacting the components (A-1), (A-2), (B) and (C) is arbitrary, and two of these components may be contacted first, followed by the remaining components, or all four components may be contacted at the same time. In order to ensure sufficient contact, a solvent may be used. Examples of the solvent include inert hydrocarbon solvents such as aliphatic saturated hydrocarbons, aromatic hydrocarbons and aliphatic unsaturated hydrocarbons, as well as halides thereof and prepolymerized monomers. Examples of the aliphatic saturated hydrocarbons and aromatic hydrocarbons include hexane, heptane and toluene.

[0067] 6. Prepolymerization The propylene polymerization catalyst is preferably subjected to prepolymerization by contacting with an olefin and polymerizing a small amount of the propylene polymerization catalyst. Prepolymerization can improve the catalytic activity and reduce the production cost. The olefin to be used is not particularly limited, but examples thereof include ethylene, propylene, 1-butene, 1-hexene, 1-octene, 4-methyl-1-pentene, 3-methyl-1-butene, vinylcycloalkane, styrene, etc., and preferably propylene. The olefin may be fed into the prepolymerization reactor at a constant rate or at a constant pressure, or any combination thereof, or by changing the rate stepwise. The prepolymerization temperature and prepolymerization time are not particularly limited, but are preferably in the range of −20° C. to 100° C. and 5 minutes to 24 hours, respectively. The amount of prepolymerization is preferably 0.01-100, more preferably 0.1-50, in terms of the mass ratio of the prepolymerized polymer to the component (B). Also, component (C) can be added during the prepolymerization. During or after the contact of the above components, a polymer such as polyethylene or polypropylene or a solid inorganic oxide such as silica or titania may be allowed to coexist. The catalyst may be dried after the preliminary polymerization. The drying method is not particularly limited, and examples thereof include drying under reduced pressure, drying by heating, and drying by passing a dry gas through the catalyst. These methods may be used alone or in combination of two or more methods. In the drying step, the catalyst may be stirred, vibrated, fluidized, or left to stand.

[0068] II. Poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymers The poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer supplied in the method for producing a propylene-based polymer of the present invention is represented by the following general formula (I). Formula (I):HO-(C3H6O) a -(C2H4O) b -(C3H6O) c -H [In the general formula (I), a and c each independently represent an integer of 1 to 60, b represents an integer of 1 to 29, and a+c=2 to 120, and a+b+c≧3 are satisfied.]

[0069] In the method for producing a propylene-based polymer of the present invention, the specific PPG-PEG-PPG block copolymer is added to the propylene polymerization catalyst containing the specific two or more metallocene compounds, thereby maintaining the ratio of the polymers produced from the metallocene compounds, and the aggregation of polymer powder and adhesion to the reactor during polymerization are suppressed while maintaining the physical properties of the resulting branched propylene-based polymer. The reason why this effect is excellent is unclear, but can be considered as follows. The PPG-PEG-PPG block copolymer is more soluble in hydrophobic hydrocarbon solvents than, for example, the PEG-PPG-PEG block copolymer, and is easier to supply during polymerization. Furthermore, since the hydrophobic PPG is located on the outside of the PPG-PEG-PPG block copolymer, it has a high affinity with propylene, and in propylene polymerization, it has good dispersibility in a polymerization reactor. It is believed that the PPG-PEG-PPG block copolymer, well dispersed in the polymerization reactor, protects the surface of the catalyst particles, preventing contact between catalyst particles and improving the dispersion of the catalyst. The mechanism for protecting the catalyst particle surface is not clear, but it is believed that the hydrophobic PPG chains are attracted to the surrounding liquefied propylene, and the hydrophilic PEG chains act on the catalyst particles, covering the catalyst surface with polymers, making it easier to prevent contact between catalyst particles. When catalysts are located close to each other, the heat of the exothermic reaction in which the polymer grows can cause the polymer to melt and easily form agglomerates. However, in the present invention, the catalyst is well dispersed in the polymerization reactor, which is thought to suppress agglomeration of the polymer powder during polymerization. In addition, in the present invention, the highly conductive PPG-PEG-PPG block copolymer covers the surface of the catalyst particles, which is thought to make it difficult for the grown polymer powder to become charged, thereby suppressing the adhesion of the polymer powder to the reactor wall. On the other hand, the PPG-PEG-PPG block copolymer in which the hydrophobic PPG is arranged on the outside is more likely to react equally with the two metallocene compounds, component (A-1) and component (A-2), for reasons that are not clear, and this is thought to enable the ratio of polymer production amounts derived from each metallocene compound to be maintained, and the physical properties of the branched propylene polymer to be maintained.

[0070] In the general formula (I), a and c each independently represent an integer of 1 to 60, and a+c=2 to 120. The PPG portion, which is a hydrophobic group, is considered to provide dispersibility in liquefied propylene. In terms of handling during production, such as adjusting viscosity, a+c is preferably 100 or less, more preferably 80 or less. In terms of hydrophobic function, a and c may each independently be 2 or more, and a+c is preferably 10 or more, more preferably 20 or more.

[0071] In the general formula (I), b is an integer of 1 to 29. The hydrophilic PEG moiety is thought to provide properties such as a reduction in surface potential resistance as a surfactant. From the viewpoint of hydrophilic function, b is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. In order to prevent the solubility in liquefied propylene from decreasing too much, b is preferably 25 or less, more preferably 20 or less, and even more preferably 15 or less.

[0072] In the general formula (I), from the viewpoint of suppressing a decrease in catalytic activity, it is preferable that a+c>b.

[0073] a+b+c is 3 or more, but may be 4 or more, or may be 5 or more. On the other hand, from the viewpoint of handleability during production, a+b+c is 120 or less, but may be 110 or less, or may be 100 or less. From the viewpoints of suppressing a decrease in catalytic activity, easiness in maintaining the physical properties of the obtained branched propylene polymer, and improving the effect of suppressing aggregation and adhesion of polymer powder, a+b+c is preferably 10 to 80, and more preferably 20 to 70.

[0074] From the viewpoint of suppressing a decrease in catalytic activity, the number average molecular weight of the PPG-PEG-PPG block copolymer used in the present invention has a lower limit of 500 or more, more preferably 700 or more, and even more preferably 900 or more, and may be 1200 or more, or may be 1500 or more. On the other hand, from the viewpoint of dispersibility of the PPG-PEG-PPG block copolymer in liquefied propylene, the upper limit is 8000 or less, preferably 6000 or less, and more preferably 5000 or less. Any combination of the upper and lower limits can be adopted.

[0075] The PPG-PEG-PPG block copolymer used in the present invention may be a commercially available product that is appropriately selected and used. Examples of commercially available products include those sold under the trade names Poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol) (Sigma-Aldrich), Pluronic (registered trademark, BASF), and Adeka Pluronic (registered trademark, ADEKA), and examples of such structures include 31R1, 25R1, 10R5, 10R8, 17R2, 17R4, 25R2, and 25R4.

[0076] III. Method for producing propylene polymer The method for producing a propylene-based polymer of the present invention is a method for producing a propylene-based polymer, which comprises supplying the specific PPG-PEG-PPG block copolymer to a polymerization system and continuously polymerizing propylene in the presence of the specific propylene polymerization catalyst.

[0077] The polymerization method may be any method that efficiently contacts propylene with the propylene polymerization catalyst containing the above-mentioned components (A-1), (A-2), (B) and (C). So-called bulk polymerization, in which propylene is used as a solvent without substantially using an inert solvent, is preferred. For example, in the case of bulk polymerization, the lower limit of the polymerization temperature is preferably 40° C. or more, more preferably 50° C. or more. The upper limit is preferably 80° C. or less, more preferably 75° C. or less. The lower limit of the polymerization pressure is preferably 1.0 MPa or more, more preferably 1.5 MPa or more, and even more preferably 2.0 MPa or more. The upper limit is preferably 5.0 MPa or less, more preferably 4.0 MPa or less, and even more preferably 3.5 MPa or less. The polymerization may be a single-stage polymerization or a multi-stage polymerization.

[0078] The propylene-based polymer produced by the production method of the present invention may be a propylene homopolymer or a copolymer of propylene and one or more comonomers selected from α-olefins having 2 to 20 carbon atoms other than propylene. Examples of the α-olefins having 2 to 20 carbon atoms other than propylene include ethylene, 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene.

[0079] The production method of the present invention includes at least a step of continuously withdrawing a propylene-based polymer from a polymerization reactor while continuously introducing propylene into the polymerization reactor, where "continuously" includes not only constantly supplying / withdrawing but also intermittently supplying / withdrawing.

[0080] [Introduction of propylene] The method for continuously introducing propylene into the polymerization reactor is not particularly limited, but may be, for example, a method in which liquefied propylene is fed from the top of the polymerization reactor using a pump. Alternatively, liquefied propylene may be supplementarily fed in portions from a catalyst feed pipe or a hydrogen pipe in an amount less than the amount fed from the top of the polymerization reactor.

[0081] [Introduction of the specific PPG-PEG-PPG block copolymer] In the production method of the present invention, there is no particular limitation on the method, supply location, and timing of supplying the PPG-PEG-PPG block copolymer during polymerization, as long as the specific PPG-PEG-PPG block copolymer can be supplied into the polymerization system. The PPG-PEG-PPG block copolymer may be mixed with a catalyst and supplied to a polymerization reactor, or may be directly supplied to a polymerization reactor separately from the catalyst. When multi-stage polymerization is performed using multiple reactors, the PPG-PEG-PPG block copolymer may be supplied to all reactors, or may be supplied only to a specific reactor. The PPG-PEG-PPG block copolymer may be supplied to piping through which a catalyst, a solvent, or a monomer flows, or may be supplied to a part where adhesion or clogging is particularly likely to be a problem, such as a heat exchanger, a filter, or a pressure gauge. The PPG-PEG-PPG block copolymer may be supplied continuously or intermittently. A preferred method is to merge the PPG-PEG-PPG block copolymer into a catalyst supply pipe and then supply it to a polymerization reactor. Since the PPG-PEG-PPG block copolymer has the effect of preventing adhesion between catalyst particles, by previously merging the PPG-PEG-PPG block copolymer into a catalyst supply pipe and then supplying it to a polymerization reactor, the contact efficiency with the catalyst is improved, and the effect of suppressing the aggregation of polymer powder and adhesion to the reactor wall is easily exhibited.

[0082] Furthermore, when the PPG-PEG-PPG block copolymer is supplied to the polymerization system, in terms of adjusting the viscosity and the amount added, the PPG-PEG-PPG block copolymer may be diluted or dissolved in a hydrocarbon solvent to prepare a solution, and the solution may be supplied to the polymerization system. As the hydrocarbon solvent, saturated aliphatic or aromatic hydrocarbons such as hexane, heptane, pentane, cyclohexane, benzene, and toluene may be used alone or in mixture. Furthermore, in order to adjust the solubility in the solvent and the viscosity, the temperature may be adjusted by heating, cooling, or the like. The concentration of the PPG-PEG-PPG block copolymer when preparing a solution by diluting or dissolving the PPG-PEG-PPG block copolymer in a hydrocarbon solvent may be appropriately selected depending on the viscosity of the solution depending on the temperature and the amount added. The concentration of the PPG-PEG-PPG block copolymer when preparing a solution can be set as Y≦0.1X+0.5, where Y is the concentration (mass%) and X is the solution temperature (°C) when diluting. Here, X may be 0°C or higher.

[0083] Among these, it is preferable to merge the PPG-PEG-PPG block copolymer diluted or dissolved in a hydrocarbon solvent into a catalyst supply pipe and supply it to the polymerization reactor, since this is more likely to exert the effect of suppressing aggregation of the polymer powder and adhesion to the reactor wall. The PPG-PEG-PPG block copolymer diluted or dissolved in a hydrocarbon solvent may be joined to a catalyst supply pipe, and then the catalyst supply pipe may be joined to a propylene supply pipe, so that the PPG-PEG-PPG block copolymer, the catalyst, and propylene are simultaneously supplied to the polymerization reactor. When the PPG-PEG-PPG block copolymer diluted or dissolved in a hydrocarbon solvent is allowed to join the catalyst supply pipe, it may be allowed to join just before being supplied to the polymerization reactor in order to suppress the effect on the catalyst.

[0084] In the method for producing a propylene-based polymer of the present invention, the amount of the PPG-PEG-PPG block copolymer fed into the polymerization system is not particularly limited, but from the viewpoint of suppressing a decrease in catalytic activity and improving the effect of suppressing aggregation and adhesion of polymer powder to the reactor wall, the feed ratio of the PPG-PEG-PPG block copolymer to the feed amount of the propylene may be set to 0.1 mass ppm to 10 mass ppm. If the feed ratio of the PPG-PEG-PPG block copolymer is 10 mass ppm or less, it is also possible to suppress an increase in the load of recovery and purification treatment of the polymerization solvent and gas. In order to improve the effect of suppressing aggregation and adhesion to the reactor wall surface of the polymer powder and to more easily prevent pipe clogging problems, the ratio of the supply amount of the PPG-PEG-PPG block copolymer to the supply amount of propylene may be 1.0 ppm by mass or more, 1.5 ppm by mass or more, or 3.0 ppm by mass or more.

[0085] [Introduction of hydrogen] Hydrogen may also be used as a molecular weight regulator. When hydrogen is continuously introduced into the polymerization reactor, hydrogen can be introduced into the gas phase, the liquid phase, or both in the polymerization reactor. In the production method of the present invention, hydrogen is preferably introduced directly into the liquefied propylene, since it is easy to keep the ratio of the introduction flow rate of hydrogen to propylene constant. In this case, the place where hydrogen is introduced can be any place in the vertical or horizontal direction in the propylene liquid in the polymerization reactor.

[0086] Polymerization pressure is 0kg / cm 2 ~2000kg / cm 2 G (≒0MPaG to 196.14MPaG), preferably 0kg / cm 2 ~60kg / cm 2 G (≒0MPaG~5.88MPaG) is appropriate.

[0087] Suitable examples of the propylene polymer obtained by the above-mentioned method for producing a propylene polymer include a propylene homopolymer, a propylene-ethylene block copolymer, a propylene-ethylene random copolymer, and a propylene / ethylene-olefin copolymer.

[0088] IV. Propylene-Based Polymers The propylene polymer produced by the present invention can maintain the ratio of polymer production amounts derived from each metallocene compound by the PPG-PEG-PPG copolymer used in the present invention being easily uniformly reacted with the two metallocene compounds, component (A-1) and component (A-2), and therefore the physical properties of the produced branched propylene polymer can be maintained, and the physical properties are not limited. The propylene polymer produced by the present invention may have, for example, the following physical properties.

[0089] 1.Liquidity The propylene polymer produced in the present invention may have a melt flow rate (MFR) of 0.01 g / 10 min or more and 100 g / 10 min or less, measured at a temperature of 230° C. under a load of 2.16 kg. MFR is an index that indicates the fluidity of a polymer when melted, and varies depending on the average molecular weight, molecular weight distribution, and branching structure of the polymer. The melt flow rate (MFR) can be determined by the method described in the Examples below.

[0090] 2.Molecular weight distribution Mw / Mn The propylene polymer produced in the present invention may have a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) [Mw / Mn], determined by gel permeation chromatography (GPC), of 2.5 or more and 10.0 or less. The molecular weight distribution Mw / Mn can be measured by gel permeation chromatography (GPC) in the same manner as the above-mentioned number average molecular weight (Mn).

[0091] 3.Branching structure Branching distribution The propylene-based polymer produced by the present invention has a branching index g' of preferably 0.6 to 0.9, more preferably 0.65 to 0.85, in the range of Log(molecular weight)=6 to 6.5 in a molecular weight distribution curve obtained by absolute molecular weight (Mabs) measurement by MALLS obtained by 3D-GPC. The branched propylene polymer produced by the present invention has a branching distribution within the above range, so that the melt tension can be controlled within a specific range, and the fluidity and extensibility are improved. The branching index can be determined by the method described in the Examples below.

[0092] 4. Melt tension The propylene polymer produced in the present invention may have a melt tension at MT230°C of 1.5 g or more and 40 g or less. In order to obtain a propylene polymer having excellent extensibility while maintaining a melt tension necessary for molding, the lower limit of MT230°C may be 3.6 g or more. The melt tension can be determined by the method described in the Examples below. EXAMPLES

[0093] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples as long as they do not deviate from the gist of the invention. The measurement methods in these examples are as follows.

[0094] [Various physical property measurement methods] 1. MFR (Melt Flow Rate) The MFR was measured in accordance with JIS K6921-2 "Plastics - Polypropylene (PP) molding and extrusion materials - Part 2: Preparation of test pieces and determination of properties" under test conditions of 230°C and a load of 2.16 kgf.

[0095] 2. Branching index (g') The branch structure was measured by 3D-GPC, which is a GPC apparatus connected to a differential refractometer (RI), a viscometer, and a multi-angle laser light scattering detector (MALLS). The GPC apparatus used was an Alliance GPCV2000 manufactured by Waters, equipped with a differential refractometer (RI) and a viscometer, and the light scattering detector used was a multi-angle laser light scattering detector (MALLS) DAWN-E manufactured by Wyatt Technology. The detectors were connected in the following order: MALLS, RI, and Viscometer. The mobile phase solvent was 1,2,4-trichlorobenzene (containing the antioxidant Irganox 1076 manufactured by BASF Japan at a concentration of 0.5 mg / mL). The flow rate was 1 mL / min, and two Tosoh GMHHR-H(S)HT columns were used, connected in series. The temperatures of the column, the sample injection part and each detector were set to 140°C. The sample concentration was 1 mg / mL, and the injection volume (sample loop volume) was 0.2175 mL. The absolute molecular weight (Mabs), the root mean square radius of gyration (Rg) obtained from MALLS, and the intrinsic viscosity ([η]) obtained from Viscometer were calculated using the data processing software ASTRA (version 4.73.04) attached to MALLS, with reference to the following literature. References: 1.Developments in polymer characterization, vol.4. Essex: Applied Science; 1984. Chapter1. 2.Polymer, 45, 6495-6505(2004) 3.Macromolecules, 33, 2424-2436(2000) 4.Macromolecules, 33, 6945-6952(2000)

[0096] <Calculation of branching index (g')> The branching index g' was calculated as the ratio ([η]br / [η]lin) of the intrinsic viscosity ([η]br) obtained by measuring the sample with the above-mentioned Viscometer to the intrinsic viscosity ([η]lin) obtained by separately measuring a linear polymer. When a long chain branch structure is introduced into a polymer molecule, the radius of gyration becomes smaller compared to a linear polymer molecule of the same molecular weight. Since a smaller radius of gyration results in a smaller intrinsic viscosity, the ratio ([η]br / [η]lin) of the intrinsic viscosity of the branched polymer to that of the linear polymer of the same molecular weight ([η]lin) becomes smaller as the long chain branch structure is introduced. Therefore, when the branching index g' ([η]br / [η]lin) is less than 1.0, it means that the polymer has a long chain branched structure. As the linear polymer to obtain [η]lin, a commercially available homopolypropylene (Novatec PP (registered trademark) grade name: FY6 manufactured by Japan Polypropylene Corporation) was used. It is known that the logarithm of [η]lin of a linear polymer has a linear relationship with the logarithm of the molecular weight, as known as the Mark-Houwink-Sakurada equation, so that the value of [η]lin can be obtained by appropriately extrapolating to the low molecular weight side or the high molecular weight side. In addition, when the branching index g' ([η]br / [η]lin) was calculated to be 1.0 or more, it was treated as 1.0 because it cannot theoretically be greater than 1.0, which is the value for a linear chain.

[0097] 3. GPC The weight average molecular weight (Mw), number average molecular weight (Mn), z-average molecular weight (Mz), the ratio of Mw to Mn [Mw / Mn], and the ratio of Mz to Mw [Mz / Mw] were measured by gel permeation chromatography (GPC) in the same manner as for the above-mentioned number average molecular weight (Mn).

[0098] <Method of calculating the ratio of polymers derived from component (A-1) and component (A-2)> The molecular weight distribution curve of a propylene-based polymer obtained by GPC measurement is substantially composed of two or three peaks. The peak on the lowest molecular weight side is a peak derived from component (A-1), the second peak is a peak derived from component (A-2), and the third peak is a peak containing a long chain branch formed by polymerizing the macromonomer of component (A-1) with component (A-2), but this is also considered to be a peak derived from component (A-2). The ratio of the peak derived from component (A-1) to the sum of the peak derived from component (A-1) (i.e., the peak on the lowest molecular weight side) and the peak derived from component (A-2) (i.e., the second and third peaks) is defined as the ratio of the polymer generated from component (A-1) [= amount of polymer derived from component (A-1) / [amount of polymer derived from component (A-1)+amount of polymer derived from component (A-2)].

[0099] The ratio of each peak was measured by the following method using the molecular weight distribution curve (G1) of a propylene polymer obtained by polymerization using a catalyst containing components (A-1), (A-2), (B) and (C) and the molecular weight distribution curve (G2) of a propylene polymer obtained by polymerization under the same conditions as those for obtaining the propylene polymer (G1), except that a catalyst not containing the component (A-2) was used. In the present invention, the term "molecular weight distribution curve" may refer to a differential molecular weight distribution curve unless otherwise specified. In addition, when the "area" of a molecular weight distribution curve is referred to, it refers to the area of ​​the region formed between the molecular weight distribution curve and the baseline.

[0100] [1] For each of the numerical data (G1) and (G2), log(molecular weight) is divided into intervals of 0.025, and the intensity [dwt / dlog(molecular weight)] is normalized so that the area is 1 for each of (G1) and (G2).

[0101] [2] At this time, on the low molecular weight side (log(molecular weight) = 4.0 or less), the intensity of (G2) at each molecular weight is arbitrarily changed by a certain ratio (x times) so that the absolute value of the difference between the intensity of (G1) and the intensity of (G2) at each molecular weight is approximately 0.01 or less.

[0102] [3] Ratio of peaks derived from component (A-1) W A-1 , the ratio of peaks originating from component (A-2) W A-2 is calculated as follows: W A-1 =S(G1) W A-2 =S(G2) where S(G1) is the area of ​​(G1) after changing the intensity.

[0103] That is, if the intensity of (G1) is multiplied by x, S(G1) and S(G2) become x and 1-x, respectively. Therefore, W A-1 and W A-2 can be expressed as follows, respectively: W A-1 =x W A-2 =1-x

[0104] 4. Melt tension (MT) The melt tension (MT) was measured at 230°C (MT230°C). The melt tension was measured using a melt tension tester (e.g., Capilograph 1B manufactured by Toyo Seiki Co., Ltd.) at a resin temperature of 230°C, by extruding the resin in a string shape under the following conditions, and winding it up on a roller. The tension detected on the pulley was taken as the melt tension (MT230°C). Capillary: diameter 2.1 mm Cylinder diameter: 9.6mm Cylinder extrusion speed: 10mm / min Winding speed: 4.0m / min In addition, if breakage occurs at a winding speed of 4.0 m / min, the melt tension cannot be evaluated.

[0105] 5. Bulk density Bulk density was measured according to ASTM 1895-96 TEST METHOD A.

[0106] 6. Powder clumping The presence or absence of powder agglomerates was confirmed by observation with an optical microscope (Keyence VHX-7000). The powder was placed on a sample stage so that it did not overlap, and observed at a magnification of 500 times to confirm the presence or absence of powder agglomerates due to melting.

[0107] 7. Lump amount The polymer obtained by polymerization was placed in a vibrating sieve particle size measuring device in accordance with JIS Z 8801-1:2000 and thoroughly shaken, and the weight of the polymer remaining on the sieve was measured and calculated according to the following formula. Amount of lump (wt%) = Amount of polymer remaining on the sieve ÷ Amount of polymer put into the sieve × 100 The sieve had an opening of 710 μm.

[0108] 8.Average particle size The average particle size of the polymer powder was measured using a Microtrac image analysis type particle size distribution measuring device, Camsizer. 30 g of polymer powder was used as the measurement sample, and the measurement sample was allowed to fall freely in small amounts from the sample feeder at the top of the device, and the falling measurement sample was continuously photographed by a CCD camera. The photographed images were analyzed using software attached to the device to derive the particle size of the measurement sample. In the present invention, the volume-based median diameter (D50) was used as the average particle size of the polymer powder.

[0109] (Synthesis Example 1: Preparation of Component (A-1) (Complex 1)) (1) Synthesis of Complex 1 As component (A-1) (complex 1), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-i-propylphenyl)indenyl}]hafnium was synthesized according to the method described in Example 13(1) of JP 2009-299046 A.

[0110] (2) Evaluation of terminal vinyl ratio (Rv) (2-1) Preparation of catalyst (2-a) Chemical treatment of ion-exchanged layered silicate Into a 1 L three-neck flask equipped with a stirring blade and a reflux device, 645.1 g of distilled water and 82.6 g of 98% sulfuric acid were added and heated to 95°C. 100 g of commercially available montmorillonite (Benclay KK manufactured by Mizusawa Chemical Industry Co., Ltd., Al=9.78% by mass, Si=31.79% by mass, Mg=3.18% by mass, Al / Si (molar ratio)=0.320, average particle size 14 μm) was added thereto, and the mixture was reacted for 320 minutes at 95° C. After 320 minutes, 0.5 L of distilled water was added to stop the reaction, and 255 g of a cake-like solid was obtained by filtration. This cake (1 g) contained 0.31 g of the chemically treated montmorillonite (intermediate). The chemical composition of the chemically treated montmorillonite (intermediate) was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, and the Al / Si (molar ratio) = 0.222. 1545g of distilled water was added to the cake to make a slurry, and the temperature was raised to 40℃. 5.734g of lithium hydroxide hydrate was added as a solid, and the reaction was carried out at 40℃ for 1 hour. After 1 hour, the reaction slurry was filtered and washed with 1L of distilled water three times, and a cake-like solid was obtained again. The collected cake was dried to obtain 80 g of chemically treated montmorillonite, which had a chemical composition of Al=7.68% by mass, Si=36.05% by mass, Mg=2.13% by mass, Al / Si (molar ratio)=0.222, and Li=0.53% by mass.

[0111] (2-b) Prepolymerization 20 g of the obtained chemically treated montmorillonite was placed in a 1 L three-neck flask, and 131 mL of heptane was added to make a slurry, to which 50 mmol of triisobutylaluminum (69 mL of a heptane solution with a concentration of 143.4 mg / mL) was added and stirred for 1 hour. After 1 hour, the mixture was washed with heptane to 1 / 100, and the total volume was made 100 mL. The slurry solution containing this chemically treated montmorillonite was kept at 50° C., and 4.2 mmol of tri-normal octylaluminum (10.6 mL of a heptane solution with a concentration of 145.0 mg / mL) was added thereto and stirred for 20 minutes. To this was added 0.3 mmol of rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-i-propylphenyl)indenyl}]hafnium (prepared as a slurry with 50 mL of toluene), and the mixture was stirred for 20 minutes while maintaining the temperature at 50°C. Then, 350 mL of heptane was added and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was raised to 40° C., propylene was introduced at a rate of 10 g / hour, and prepolymerization was carried out for 4 hours while maintaining the temperature at 40° C. Thereafter, the introduction of propylene was stopped, and residual polymerization was carried out for 1 hour while maintaining the temperature at 40° C. The supernatant of the obtained catalyst slurry was removed by decantation, and then heptane was added again and decanted to wash the prepolymerized catalyst. 12 mmol of triisobutylaluminum (16.6 mL of a heptane solution with a concentration of 143.4 mg / mL) was added to the portion remaining after the decantation and stirred for 10 minutes. The solid was dried under reduced pressure at 40°C for 2 hours to obtain 54.0 g of a dried prepolymerized catalyst. The prepolymerization ratio (the value obtained by dividing the amount of prepolymerized polymer by the amount of solid catalyst) was 1.70.

[0112] (2-2) Polymerization A 3L autoclave was dried thoroughly in advance by passing nitrogen through it under heating, and then the inside of the vessel was replaced with propylene and cooled to room temperature. 2.86mL of a heptane solution of triisobutylaluminum (143.4mg / mL), 240ml of hydrogen, and 750g of liquefied propylene were introduced, and the temperature was raised to 70°C. Then, 100mg of the above catalyst, excluding the prepolymerized polymer, was pumped into the polymerization vessel with high-pressure argon to start polymerization. After holding at 70°C for 1 hour, the unreacted propylene was quickly purged to stop the polymerization. As a result, about 128g of propylene homopolymer with MFR=38 was obtained.

[0113] (2-3) Terminal vinyl ratio The terminal vinyl ratio (Rv) of the obtained propylene homopolymer was evaluated by the method described in the present specification. According to structural formula (1-a) and structural formula (1-e), [Vi] = 0.61, Mn = 63,467, and terminal vinyl ratio (Rv) = 0.92. According to structural formula (1-b), [Vd] = 0.10 and the terminal vinylidene ratio (Rvd) = 0.15.

[0114] (Synthesis Example 2: Preparation of Component (A-2) (Complex 2)) (1) Synthesis of Complex 2 As component (A-2) (complex 2), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium was synthesized according to the method described in Example 7 of JP-A-11-240909.

[0115] (2) Evaluation of terminal vinyl ratio (Rv) (2-1) Preparation of catalyst (2-a) Chemical treatment of ion-exchanged layered silicate The chemical treatment was carried out in the same manner as in the evaluation of the terminal vinyl ratio of the above-mentioned component (A-1) (complex 1) for the ion-exchangeable layered silicate. (2-b) 20 g of the obtained chemically treated montmorillonite was placed in a 1 L three-neck flask, and 131 mL of heptane was added to make a slurry, to which 50 mmol of triisobutylaluminum (69 mL of a heptane solution with a concentration of 143.4 mg / mL) was added and stirred for 1 hour. After 1 hour, the mixture was washed with heptane to a volume of 1 / 100, and the total volume was adjusted to 100 mL. The slurry solution containing this chemically treated montmorillonite was kept at 50° C., and 4.2 mmol of tri-normal octylaluminum (10.6 mL of a heptane solution with a concentration of 145.0 mg / mL) was added thereto and stirred for 20 minutes. To this was added 0.3 mmol of rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (prepared as a slurry with 50 mL of toluene), and the mixture was stirred for 20 minutes while maintaining the temperature at 50°C. Then, 350 mL of heptane was added and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was raised to 40° C., propylene was introduced at a rate of 10 g / hour, and prepolymerization was carried out for 4 hours while maintaining the temperature at 40° C. Thereafter, the introduction of propylene was stopped, and residual polymerization was carried out for 1 hour while maintaining the temperature at 40° C. The supernatant of the obtained catalyst slurry was removed by decantation, and then heptane was added again and decanted to wash the prepolymerized catalyst. 12 mmol of triisobutylaluminum (16.6 mL of a heptane solution with a concentration of 143.4 mg / mL) was added to the portion remaining after the decantation and stirred for 10 minutes. The solid was dried under reduced pressure at 40°C for 2 hours to obtain 62.2 g of a dried prepolymerized catalyst. The prepolymerization ratio (the value obtained by dividing the amount of prepolymerized polymer by the amount of solid catalyst) was 2.11.

[0116] (2-2) Polymerization A 3L autoclave was thoroughly dried in advance by passing nitrogen through it under heating, and then the inside of the vessel was replaced with propylene and cooled to room temperature. 2.86mL of a heptane solution of triisobutylaluminum (143.4mg / mL), 240ml of hydrogen, and 750g of liquefied propylene were introduced, and the temperature was raised to 70°C. Then, 30mg of the above catalyst, excluding the prepolymerized polymer, was pumped into the polymerization vessel with high-pressure argon to start polymerization. After holding at 70°C for 1 hour, the unreacted propylene was quickly purged to stop the polymerization. As a result, about 157g of propylene homopolymer with MFR=1.0 was obtained.

[0117] (2-3) Terminal vinyl ratio The terminal vinyl ratio (Rv) of the obtained propylene homopolymer was evaluated by the method described in the present specification. According to structural formula (1-a) and structural formula (1-e), [Vi] = 0, Mn = 148,356, and terminal vinyl ratio (Rv) = 0. According to structural formula (1-b), [Vd] was 0.17 and the terminal vinylidene ratio (Rvd) was 0.6.

[0118] (Preparation Example 1: Preparation of propylene polymerization catalyst) (1) Chemical treatment of ion-exchanged layered silicate The chemical treatment of the ion-exchanged layered silicate in the evaluation of the terminal vinyl ratio of the component (A-1) (complex 1) was carried out in the same manner to obtain 80 g of chemically treated montmorillonite. The chemical composition of this chemically treated montmorillonite was Al=7.68% by mass, Si=36.05% by mass, Mg=2.13% by mass, Al / Si (molar ratio)=0.222, Li=0.53% by mass.

[0119] (2) Prepolymerization 20 g of the above-obtained chemically treated montmorillonite was placed in a three-neck flask (volume 1 L), and heptane (131 mL) was added to make a slurry, to which 50 mmol of triisobutylaluminum (69 mL of a heptane solution with a concentration of 143.4 mg / mL) was added and stirred for 1 hour. After 1 hour, the mixture was washed with heptane to 1 / 100, and the total volume of the slurry solution containing the chemically treated montmorillonite was brought to 100 mL and the temperature was maintained at 50°C. 432 μmol of triisobutylaluminum (0.6 mL of a heptane solution with a concentration of 143.4 mg / mL) was added to the slurry solution and stirred for 5 minutes. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (108 μmol) prepared in Synthesis Example 2 of the catalyst component (A-2) was dissolved in toluene (33 mL) to prepare solution 1. The solution 1 was added to the slurry solution in the 1 L flask and stirred for 60 minutes while maintaining the temperature at 50°C. Furthermore, 3528 μmol of tri-normal octylaluminum (8.9 mL of a heptane solution with a concentration of 145.0 mg / mL) was added to the slurry solution and stirred for 10 minutes. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-i-propylphenyl)indenyl}]hafnium (252 μmol) prepared in Synthesis Example 1 of the catalyst component (A-1) was dissolved in toluene (36 mL) to prepare solution 2. The solution 2 was added to the slurry solution in the 1 L flask and stirred for 20 minutes while maintaining the temperature at 50°C. Then, 321 mL of heptane was added to the slurry solution, and the slurry was introduced into a 1 L autoclave. The solid component in the slurry was the solid catalyst. After the internal temperature of the autoclave was raised to 40° C., propylene was introduced at a flow rate of 10 g / hr, and prepolymerization was carried out for 4 hours while maintaining the temperature at 40° C. Thereafter, the introduction of propylene was stopped, and residual polymerization was carried out for 1 hour while maintaining the temperature at 40° C. The supernatant of the obtained catalyst slurry was removed by decantation, and then heptane was added again and decanted to wash the prepolymerized catalyst. 12 mmol of triisobutylaluminum (16.6 mL of a heptane solution with a concentration of 143.4 mg / mL) was added to the portion remaining after the decantation and stirred for 10 minutes. This solid was dried under reduced pressure at 40°C for 2 hours to obtain 62.0 g of a dried prepolymerized catalyst (prepolymerized catalyst 1). The prepolymerization ratio of prepolymerized catalyst 1 (the value obtained by dividing the weight of the prepolymerized polymer by the weight of the solid catalyst (approximated by the weight of the chemically treated montmorillonite)) was 2.10.

[0120] (Example 1: Production of propylene polymer) Internal volume 100m 3 Into a stirred high-pressure reactor (L / D=1.2), liquefied propylene was continuously introduced at a flow rate of 20.8 T / hr, triisobutylaluminum at 80 kg / hr, hydrogen at 0.110 kg / hr (hydrogen / propylene=111 mol ppm), and solid catalyst at 1.7 kg / hr, and polymerization was carried out at a temperature of 70°C. During the polymerization, a hexane solution (PPG-PEG-PPG block copolymer concentration: 0.75 wt %) of a PPG-PEG-PPG block copolymer (trade name: poly(propylene glycol)-block-poly(ethylene glycol)-block-poly(propylene glycol), available from Sigma-Aldrich, number average molecular weight approximately 3,300, a+c=48, a≧1, c≧1, b=12) was continuously introduced into the reaction vessel at a rate of 5 kg / hr via a conduit for supplying the catalyst. The withdrawal rate of the propylene polymer (powder) was 8.3 T / hr. The obtained propylene-based polymer (powder) was thoroughly dried and then granulated under the following granulation conditions to obtain pellets of the propylene-based polymer. The obtained powder was used to measure the bulk density and average particle size, and to check for the presence or absence of aggregation. The granulated pellets were used to measure MFR, GPC, branching index g', and MT. The polymerization conditions and the measurement results are shown in Table 1.

[0121] (granulation) 100 parts by weight of the propylene polymer powder was blended with 0.125 parts by weight of tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane (product name: IRGANOX1010, manufactured by BASF Japan Ltd.), which is a phenol-based antioxidant, and 0.125 parts by weight of tris(2,4-di-t-butylphenyl)phosphite (product name: IRGAFOS 168, manufactured by BASF Japan Ltd.), which is a phosphite-based antioxidant, and mixed for 3 minutes at room temperature using a high-speed stirring mixer (product name: Henschel mixer). The mixture was then melt-kneaded in a twin-screw extruder to obtain pellets of the propylene polymer. The twin-screw extruder used was a Technobel KZW-25, with a screw rotation speed of 400 RPM and kneading temperatures set at 80, 160, 210, and 230°C from the bottom of the hopper (the same temperature was maintained from then until the die exit).

[0122] Comparative Example 1 A propylene-based polymer (powder) was obtained in the same manner as in Example 1, except that the hexane solution of the PPG-PEG-PPG block copolymer was not joined to the catalyst supply pipe during the polymerization. Propylene-based polymer pellets were obtained by granulation under the above granulation conditions in the same manner as in Example 1. The obtained powder was used to measure the bulk density and average particle size, and to check for the presence or absence of aggregation. The granulated pellets were used to measure MFR, GPC, branching index g', and MT.

[0123] (Examples 2 and 3) During the polymerization, the same procedure as in Example 1 was carried out except that the amounts of hydrogen and prepolymerization catalyst fed were changed as shown in Table 1, to obtain a propylene-based polymer (powder). Propylene-based polymer pellets were obtained by granulation under the above granulation conditions in the same manner as in Example 1. The obtained powder was used to measure the bulk density and average particle size, and to check for the presence or absence of aggregation. The granulated pellets were used to measure MFR, GPC, branching index g', and MT.

[0124] (Comparative Examples 2 and 3) A propylene-based polymer (powder) was obtained in the same manner as in Examples 2 and 3, except that the hexane solution of the PPG-PEG-PPG block copolymer was not joined to the catalyst supply pipe during the polymerization. Propylene-based polymer pellets were obtained by granulation under the above granulation conditions in the same manner as in Example 1. The obtained powder was used to measure the bulk density and average particle size, and to check for the presence or absence of aggregation. The granulated pellets were used to measure MFR, GPC, branching index g', and MT.

[0125] The polymerization conditions and the measurement results are shown in Table 1.

[0126] [Table 1]

[0127] In a method for producing a propylene-based polymer by continuously polymerizing propylene in the presence of a propylene polymerization catalyst containing the components (A-1), (A-2), (B) and (C), a PPG-PEG-PPG block copolymer was added at 1.8 wtppm relative to the amount of propylene in the polymerization system in Example 1, and no PPG-PEG-PPG block copolymer was added to the polymerization system in Comparative Example 1. In Example 1 and Comparative Example 1, propylene-based polymers were produced under the same conditions except for the presence or absence of the PPG-PEG-PPG block copolymer. In the production of the propylene-based polymer in Example 1, a PPG-PEG-PPG block copolymer was added, but the polymer production ratio between the polymer derived from component (A-1) and the polymer derived from component (A-2) was 0.80 / 0.20, which was shown to be maintained at the same polymer production ratio as in Comparative Example 1, in which no component (A-1) was added. The measurement results of MFR, branching index, MT, and GPC of the propylene-based polymer obtained in Example 1 were respectively equivalent to those of the propylene-based polymer obtained in Comparative Example 1, and it was shown that the unique polymer terminal structure of the propylene-based polymer having long chain branches was maintained even when the PPG-PEG-PPG block copolymer was added to the polymerization system. The polymer powder of Comparative Example 1 had many powder aggregates in microscopic observation, the ratio of particles of 710 μm or more in sieve particle size distribution was 17%, adhesion to the wall surface of the withdrawal pipe after 7 days of continuous operation, and a bulk density of 0.48 g / mL. In contrast, the polymer powder of Example 1 had almost no powder aggregates in microscopic observation, the ratio of particles of 710 μm or more in sieve particle size distribution was about 2%, adhesion to the wall surface of the withdrawal pipe after 7 days of continuous operation was not observed, the volume-based median particle size D50 was small, and the bulk density was increased to 0.51 g / mL. In Comparative Example 1, in which there was a lot of powder agglomeration, with the ratio of particles of 710 μm or more being 17% in the sieve particle size distribution, and adhesion to the wall surface of the withdrawal piping after 7 days of continuous operation, it was expected that if production operation was continued, the withdrawal piping would be clogged and operation would not be able to be continued.In contrast, in Example 1, the agglomeration of powder was suppressed, and there was no adhesion to the wall surface of the withdrawal piping after 7 days of continuous operation, demonstrating that it is possible to suppress deterioration of operability due to pipe clogging and powder adhesion to the wall surface of the withdrawal piping.

[0128] As in Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3 were also evaluated by comparing the presence or absence of addition of the PPG-PEG-PPG block copolymer. As a result, it was shown that in the production of the propylene-based polymer in the examples, the PPG-PEG-PPG block copolymer was added, but the polymer production ratio between the polymer derived from component (A-1) and the polymer derived from component (A-2) was maintained at the same polymer production ratio as in the comparative example in which no PPG-PEG-PPG block copolymer was added. The propylene-based polymers obtained in the examples had similar physical properties to the propylene-based polymers obtained in the comparative examples. The polymer powder of the comparative example had many powder aggregates in microscopic observation, a large proportion of particles 710 μm or larger in sieve particle size distribution, and adhesion to the wall surface of the withdrawal pipe after 7 days of continuous operation. In contrast, the polymer powder of the example had almost no powder aggregates in microscopic observation, a small proportion of particles 710 μm or larger in sieve particle size distribution, no adhesion to the wall surface of the withdrawal pipe after 7 days of continuous operation, a smaller median particle size D50 than the comparative example, and an increased bulk density. In the Comparative Example, in which there was a large amount of powder agglomeration, a large proportion of particles 710 μm or larger in the sieve particle size distribution, and adhesion to the wall of the withdrawal piping after 7 days of continuous operation, it was expected that if production operation was continued, the withdrawal piping would be clogged and operation would not be able to continue.In contrast, in the Example, the agglomeration of powder was suppressed, and there was no adhesion to the wall of the withdrawal piping after 7 days of continuous operation, demonstrating that it is possible to suppress deterioration of operability due to pipe clogging and powder adhesion to the wall of the withdrawal piping. [Industrial Applicability]

[0129] INDUSTRIAL APPLICABILITY The present invention provides a method for stably producing a propylene-based polymer having long chain branches without impairing the quality of the propylene-based polymer, and has high industrial applicability.

Claims

1. A method for producing a propylene polymer, comprising continuously polymerizing propylene in the presence of a propylene polymerization catalyst comprising the following components (A-1), (A-2), (B) and (C): A method for producing a propylene-based polymer, comprising feeding a poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer represented by the following general formula (I) into a polymerization system: HO-(C 3 H 6 O) a -(C 2 H 4 O) b -(C 3 H 6 O) c -H・・・(I) [In the general formula (I), a and c are each independently an integer of 1 to 60, b is an integer of 1 to 29, and a+c=2 to 120, and a+b+c≧3 are satisfied.] Component (A-1): A metallocene compound which forms a polymerization catalyst which produces a propylene homopolymer having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is carried out at 70°C. Here, the terminal vinyl ratio (Rv) is defined by the following formula. Rv=(Mn / 42)×[Vi] / 1000 (In the formula, Mn is the number average molecular weight determined by GPC, [Vi] is 1 It is the number of terminal vinyl groups per 1000 monomers calculated by H-NMR.) Component (A-2): A metallocene compound represented by general formula (a2). 【Chemistry 1】 [In general formula (a2), E 21 and E 22 each independently represents a cyclopentadienyl group, an indenyl group, a fluorenyl group, or an azulenyl group, each of which may have a substituent (provided that the substituent is not a heterocyclic group having 4 to 16 carbon atoms containing nitrogen, oxygen, or sulfur). 21 represents a divalent hydrocarbon group having 1 to 20 carbon atoms, or a silylene group or germylene group which may have a hydrocarbon group having 1 to 20 carbon atoms; M 21 represents zirconium or hafnium, X 21 and Y 21 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silyl group having a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, an amino group, or an alkylamino group having 1 to 20 carbon atoms.] Component (B): a compound or ion-exchangeable layered silicate that reacts with component (A-1) and component (A-2) to form an ion pair. Component (C): An organoaluminum compound.

2. The method for producing a propylene-based polymer according to claim 1, wherein a ratio of the poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer to the amount of propylene fed is 0.1 ppm by mass to 10 ppm by mass.

3. The method for producing a propylene-based polymer according to claim 1 or 2, wherein the poly(propylene glycol)-poly(ethylene glycol)-poly(propylene glycol) block copolymer is diluted or dissolved in a hydrocarbon solvent, and the resulting solution is joined to a catalyst supply pipe and supplied to a polymerization reactor.

Citation Information

Patent Citations

  • Method for producing propylene polymer improved in melt physical property

    JP2009057542A

  • Process for producing olefin polymer

    JP2014019825A

  • Method for producing propylene polymer, and branched propylene polymer

    JP2020189966A